RELATIONSHIP BETWEEN MEANING OF LIFE AND REAL AS WELL AS IDEAL SELF-IMAGE IN WOMEN WITH SUFFICIENT AND LOW SPORTS ACTIVITY - Martsynyak-Dorosh, Oksana; Ogińska-Bulik, Nina (PSYCHOLOGICAL JOURNAL, 2018)
Object. Obese women with low level of physical activity form their personality depending on their physical attractiveness and emotional state. The lack of self-realization generates internal anxiety and emotional eating problems. Methods. Noodynamics Test (TN-D) and Adjective Checklist (ACL). Results. Obese women with low level of physical activity unable to realize personal development on the basis of "multidimensional being and versatile formation". In an ideal self-image they manifest an excessive concentration on past failures, devaluate their own achievements, and become obsessed with physical attractiveness. Discussion. Self-acceptance is building internal tools for self-realization. The versatile vision of their experience improves the level of self-control in eating behavior and level of physical activity.